Factors Influencing the SME’s Performance - Tantri, Mitsalina; Priharta, Andry; Rustiana, Siti Hamidah; Tarmizi, M. Irfan; Sulhendri (Program Studi S3 Ilmu Manajemen, 2023)
The aim of this research is to examine the influence of organizational culture, information accounting management, innovation capability, and SME's performance in Tangerang Selatan. Additionally, it analyzes the nonlinear relationship between the variables of organizational culture, information accounting management, innovation capability, and SME's performance. The research utilizes the Structural Equation Modeling (SEM) method of analysis. The study period is 2023, and a total of 14,356 observation data were processed. The author found that organizational culture has an influence on information accounting management, information accounting management has an influence on SME's performance, organizational culture has an influence on SME's performance, organizational culture has an influence on innovation capabilities, information accounting management does not have an influence on innovation capabilities, and innovation capabilities have an influence on SME's performance. This study provides insights to policy regulators and policymakers, specifically the Ministry of Cooperatives and SMEs, to enhance the performance of SMEs in Tangerang Selatan, considering the ongoing regulatory reforms in Indonesia. The study can be regarded as an advanced research that explores the relationship between organizational culture, information accounting management, innovation capability, and SME's performance as supporting factors for national economic growth. Furthermore, it expands existing studies by considering SMEs operating in Indonesia.